Injury Prevention Considerations for Drum Kit Performance - Azar, Nadia R. (Frontiers in Psychology, 2022)
For any skilled performer to deliver their optimal performance, preparation must extend beyond task-specific skill development to include psychological skills training, physical conditioning, and injury prevention. The keynote lecture upon which this article is based (delivered at the International Symposium on Performance Science 2021) explored current research that demonstrates the importance of physical conditioning and injury prevention for drummers (i.e., percussionists who play the drum kit). Early results revealed that professional drummers’ heart rates during live performances can reach similar levels to those of other professional athletes during competitions. They also established that playing-related musculoskeletal disorders (PRMDs) are very common in drummers, particularly those affecting the upper limbs such as tendinitis and carpal tunnel syndrome. Evidence from laboratory-based studies supports non-neutral postures, repetitive movements, and exposure to hand-arm vibration as risk factors for the development of these injuries in drummers. Embedding injury prevention education within drum kit curricula is a promising strategy for reducing the rates at which drummers report experiencing PRMDs, and the barriers and facilitators that drum kit educators encounter when attempting to do so are currently under investigation. When drummers include both physical conditioning and injury prevention within their overall preparation regimen, they will maximize their potential to deliver their peak performance.